Kedudukan Dan Peran Strategis Kurikulum Dalam Sistem Pendidikan Nasional Indonesia - Raffida Aliya BP; Auren Fladhira; Mutrikahaini; Abdurrahmansyah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
The curriculum occupies a crucial position within the Indonesian National Education System as it serves as the principal foundation for organizing teaching and learning activities across all educational levels. This article seeks to examine the curriculum’s status as a regulatory framework guided by Law Number 20 of 2003 concerning the National Education System, as well as to analyze its strategic contribution to the achievement of national education objectives. The curriculum is not merely a structured plan outlining goals, subject content, and instructional methods, but also a medium for transmitting values, culture, and national character. This study applies a library research method by reviewing various regulations, theoretical perspectives, and curriculum policies implemented in Indonesia. The findings reveal that the curriculum plays a vital role in enhancing educational standards, aligning instructional practices with advancements in science and technology, and developing competent individuals with strong moral and ethical foundations. Consequently, the curriculum serves as a central component in shaping the direction and overall quality of national education